PENGARUH FAKTOR KEMAMPUAN SUMBER DAYA MANUSIA TERHADAP JUMLAH PENERIMAAN PAJAK BUMI DAN BANGUNAN (PBB) DI KABUPATEN GOWA SULAWESI SELATAN - Rosida Maedina (AkMen JURNAL ILMIAH, 2014)
The purpose of this study was to determine Is Human Ability Factors potentially increase revenues Land and Building Tax (PBB) at the Regional Revenue Office in Gowa. Research instruments such as questionnaires and interviews are also conducted on data obtained and analyzed using descriptive statistical techniques. The results showed that the factors of Human Resources (HR), either jointly or individually determine the magnitude of the amount of land and building tax receipts in Gowa.